Orientation Effects for LOS and NLOS OWC Characterisation Within Small Structures - Zaiton, AM.; Faezah, J.; Rihawi, Z. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper reports an experimental investigation of the orientation effect towards optical wireless channel parameters within small structures. The experiment has characterised the orientation effect of the line-of-sight (LOS) and non-line-of-sight (NLOS) infrared transmission when using different material and geometrical properties on significant infrared channel parameters. Two measurement setups were used, (1) the straight guiding structures, and (2) bending guiding structures, with three different bending angles (30o, 45o and 60o bend). In each of the measurement, the receiver/transmitter is rotated in the steps of 15˚ each time. The results revealed that the characteristic of the channel depends on the physical geometries, the orientation of the transmitter/receiver and also depend on reflection coefficient of the materials. The results are valid for both LOS and NLOS transmission.